MAKNA YANG HILANG DALAM TERJEMAH AL_QUR'AN: STUDI TERHADAP SURAT AL-QASHASH AYAT 10 VERSI KEMENTERIAN AGAMA REPUBLIK INDONESIA - Dalimunthe, Alwisyah (PERADA, 2023)
The translation of the Qur'an has a great contribution in understanding the Qur'an for non-Arabic people, especially Indonesians. One of the weaknesses of translating Arabic into Indonesian is the lack of Indonesian vocabulary. As a result, in some translations there is a loss of original meaning, such as in the translation of the Qur'an issued by the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI). The discussion in this article focuses on the meaning of the words "fuad" and "qalb" found in Surah al-Qashash  10 in the Ministry's translation verse. From this study, it is known that both words are translated using one word, namely "heart". In comparison with the original meaning and the interpretations of the scholars, it is known that the word "fuad" means "emotion" and "qalb" means "emotion that changes continuously". The difference in the meaning of the two words is so significant that it also affects the understanding of the content of the Qur'an. This happens because of the lack of Indonesian vocabulary, making it difficult to be the right equivalent in meaning. Thus, it is necessary to re-study the translation of the Qur'an so that it is closer to the original meaning. Terjemah al-Qur’an memiliki sumbangsih besar dalam memahami al-Qur’an bagi bangsa non-Arab khususnya bangsa Indonesia. Salah satu kelemahan menerjemahkan bahasa Arab ke bahasa Indonsia adalah minimnyanya kosakata bahasa Indonesia. Akibatnya, dalam beberapa terjemah terjadi kehilangan makna aslinya, seperti pada terjemahan al-Qur’an yang dikeluarkan oleh Kementerian Agama Republik Indonesia (Kemenag RI). Pembahasan pada artikel ini berfokus pada makna kata “fuad” dan “qalb” yang tedapat dalam surat al-Qashash ayat 10 pada terjemahan Kemenag RI itu. Dari kajian ini, diketahui bahwa kedua kata itu diterjemahkan dengan menggunakan satu kata yaitu “hati”. Sedangkan dalam perbandingan dengan makna asli serta tafsir para ulama diketahui bahwa kata itu “fuad” bermakna “emosi” dan “qalb” bermakna “emosi yang berubah terus menerus”. Perbedaan makna kedua kata itu sangat signifikan sehingga mempengaruhi pula dalam memahami kandungan al-Qur’an. Hal ini terjadi karena minimnya jumlah kosakata bahasa Indonesia sehingga sulit menjadi padanan yang tepat dalam memaknainya. Dengan demikian, perlu kiranya dilakukan kajian ulang terhadap terjamah Al-Qur’an agar  lebih mendekati terhadap makna aslinya.